HYDROTHERMAL TREATMENT OF EUCALYPTUS GRANDIS WOOD - de Freitas, Fabiana Paiva; Macedo Ladeira Carvalho, Ana Márcia; Oliveira Carneiro, Angélica de Cássia; Vital, Benedito Rocha; de Magalhães, Mateus Alves; Xisto, Mariana Fonseca (Floresta, 2019)
Among the technological alternatives to improve the quality and use of eucalyptus wood is heat treatment, as the wood has some features that may limit its use, such as dimensional instability, high anisotropy, and heterogeneous coloring. This study is aimed at evaluating the effect of time of hydrothermal treatment on physical, chemical, and mechanical properties of solid wood of Eucalyptus grandis. We used three trees of E. grandis, selecting only the heartwood, and prepared test specimens with dimensions of 30cmx8cmx3cm (length, width, and thickness). The hydrothermal treatment was performed in a Parr reactor using three reaction times (5, 15, and 25min) at 140°C. Partial removal of extractives occurred, especially in the outer layer of wood. There was an increase of up to 58% of its permeability because of the partial clearing of the vessel elements. There was no degradation of the main constituents of the wood, so loss of mechanical strength was observed. The hydrothermal treatment promoted the partial removal of the hydroxyl groups and/or a structural rearrangement of the hemicelluloses and cellulose, causing a reduction of the hygroscopicity of E. grandis.